Mechanics of thermally fluctuating membranes - J. H. Los (Nature Portfolio, 2017)
The truth about the cat in a graphene hammock Mechanical properties of graphene are important for both everyday and exotic applications, from sensors and resonators to graphene sails for interstellar travels. Textbook elasticity theory that all engineers learn and use is not applicable to atomic layers like graphene because of the crucial effect of thermal fluctuations. As a result, the Young modulus and other elastic constants of graphene are not fixed parameters of the material but strongly dependent on temperature, size and external load. Based on atomistic simulations, a group at Radboud University in The Netherlands has developed a quantitative theory of the mechanics of graphene. In particular, a one squared meter hammock made of graphene could sustain a cat weighing about three kilograms at room temperature. The derived scaling laws apply to all two-dimensional materials.